Angus x Nellore steers fed diets without roughage in feedlot - Miranda, Raiane Silva [UNESP]; Murta, Rogério Mendes; Silva, Fredson Vieira E.; Carvalho, Bernardo Altino Antero; Gonçalves, Dhemerson da Silva; da Silva, Vitor José (My University, 2023)
The objective was to compare the use of conventional diet, without roughage, based on whole corn or hydrated whole corn diets in confined uncastrated Angus x Nellore steers, having as variables, the ingestive behavior, performance, blood parameters and carcass characteristics. 24 cattle were used, with mean age 18 months and weighing 362.6 ± 22.3 kg, distributed in three treatments and kept in confinement until slaughter. The animals were fed ad libitum twice daily according to the respective diet of each treatment and the duration of the experimental period was 77 days. The animals from conventional treatment presented higher average dry matter intake (18,2 vs 10,1 vs 8,9 kg/day for conventional, whole corn and hydrated whole corn, respectively). There was no statistical difference (P> 0,05) for daily and period weight gain, carcass yield and primary cuts, pH and fat coverage. Diets without roughage altered the ingestive behavior with reduction of feeding time (3,59 vs 1,67 vs 1,60 h/day), rumination (7,17 vs 1,37 vs 1,66 h/day) and increased idle time (13,32 vs 21,03 vs 20,82 h/day) for conventional, whole corn grain and hydrated whole corn grain treatments, respectively. There was a significant effect (P<0,05) on serum concentrations of urea, total protein and cortisol. Thus, diets without roughage do not alter the performance and carcass characteristics of Angus x Nelore steers, being an alternative to beef cattle.
Novilhos Angus x Nelore alimentados com dietas sem volumoso em confinamento
Keywords: beef cattle; grain corn; industrial crossbreeding; intensive system